2016
DOI: 10.1002/glia.22991
|View full text |Cite
|
Sign up to set email alerts
|

Compromised axon initial segment integrity in EAE is preceded by microglial reactivity and contact

Abstract: Axonal pathology is a key contributor to long-term disability in multiple sclerosis (MS), an inflammatory demyelinating disease of the central nervous system (CNS), but the mechanisms that underlie axonal pathology in MS remain elusive. Evidence suggests that axonal pathology is a direct consequence of demyelination, as we and others have shown that the node of Ranvier disassembles following loss of myelin. In contrast to the node of Ranvier, we now show that the axon initial segment (AIS), the axonal domain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 106 publications
9
90
2
Order By: Relevance
“…Consistent with previous reports from our laboratory and others (Greer et al, 2013; Gutzmann et al, 2014; Clark et al, 2016), ankG labeling throughout the neocortex was restricted to the AIS and nodes of Ranvier (Figure 3B). Importantly, ankG labeling of intact YFP+ pyramidal neurons clearly delineated the AIS in sections from both sham and mTBI mice (Figures 6B,E).…”
Section: Resultssupporting
confidence: 92%
“…Consistent with previous reports from our laboratory and others (Greer et al, 2013; Gutzmann et al, 2014; Clark et al, 2016), ankG labeling throughout the neocortex was restricted to the AIS and nodes of Ranvier (Figure 3B). Importantly, ankG labeling of intact YFP+ pyramidal neurons clearly delineated the AIS in sections from both sham and mTBI mice (Figures 6B,E).…”
Section: Resultssupporting
confidence: 92%
“…However, they observed no changes in ankyrin-G, ÎČIV-spectrin and Nav1.6 expression at the AIS following demyelination (Hamada and Kole, 2015). Consistent with these findings, Clark et al (2016) also found AIS components remained intact following cuprizone-induced demyelination. In contrast, the authors discovered the proper clustering of ankyrin-G, ÎČIV-spectrin and Nav1.6 was lost at the AIS of mice after chronic exposure of experimental autoimmune encephalomyelitis (EAE), an inflammatory model of MS (Clark et al, 2016).…”
Section: Axonal Domain Proteins In Disease and Injurysupporting
confidence: 54%
“…Consistent with these findings, Clark et al (2016) also found AIS components remained intact following cuprizone-induced demyelination. In contrast, the authors discovered the proper clustering of ankyrin-G, ÎČIV-spectrin and Nav1.6 was lost at the AIS of mice after chronic exposure of experimental autoimmune encephalomyelitis (EAE), an inflammatory model of MS (Clark et al, 2016). Ultimately, the AIS is a primary target during inflammation and, in addition to demyelination of the distal axon, may contribute to inflammatory demyelinating diseases such as MS.…”
Section: Axonal Domain Proteins In Disease and Injurysupporting
confidence: 54%
“…Multiple pathological mechanisms can lead to impairment of normal AIS and nodes organization and the functional distribution of Nav and Kv channels along the axon (Buffington and Rasband, 2011; Normand and Rasband, 2015; Clark et al, 2016; Griggs et al, 2017). Mutations affecting the cytoskeletal organization typical of these structures, notably AnkG are implicated in a broad range of cognitive disorders (Normand and Rasband, 2015).…”
Section: Compartmentalized Distribution Of Vgcs In Axonsmentioning
confidence: 99%